КРИТЕРІЇ УСТАНОВЛЕННЯ РАМКОВИХ МЕЖ ПРЕДМЕТУ ЦИВІЛЬНО-ПРАВОВОГО РЕГУЛЮВАННЯ - Khakhulin, V.V. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2007)
The article systemizes principles (criteria.) for delimination of subjects on regulation of separate law branches in the law system of Ukraine which have been established in the general theory of law. Some more criteria are offered to establish the limits for the subject on civil and legal regulation under present conditions.